2020
DOI: 10.5858/arpa.2019-0626-ra
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Characteristics of Late Intraocular Lens Opacifications

Abstract: Context.— The increases in overall life expectancy and in lens surgeries performed on younger patients have resulted in a significant increase in the anticipated duration of artificial intraocular lenses (IOLs) in the eye. Thus, the physicochemical properties of the IOL become a critical issue, and several types of postoperative IOL opacifications have been reported. Objective.— To describe the microscopic characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 62 publications
0
32
1
6
Order By: Relevance
“…Dementsprechend werden heute eher andere Komplikationen beobachtet, welche im Zusammenhang mit diesen Materialien stehen. Während bei hydrophilen IOL v. a. eine Kalzifikation des Materials zur Eintrübung der Linse führen kann, überwiegt bei manchen Linsen aus hydrophobem Material das Auftreten von Glistenings [ 16 ].…”
Section: Verschiebung Der Gründe Für Die Explantation Von Intraokularlinsenunclassified
“…Dementsprechend werden heute eher andere Komplikationen beobachtet, welche im Zusammenhang mit diesen Materialien stehen. Während bei hydrophilen IOL v. a. eine Kalzifikation des Materials zur Eintrübung der Linse führen kann, überwiegt bei manchen Linsen aus hydrophobem Material das Auftreten von Glistenings [ 16 ].…”
Section: Verschiebung Der Gründe Für Die Explantation Von Intraokularlinsenunclassified
“…Furthermore, the osmolarity of the fluid around the IOL may play a role as do comorbidities of the patients such as diabetes mellitus. Inflammations or an interrupted blood-aqueous barrier may also influence the outcome in every patient [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…Glistenings describe small, refractive microvacuoles that arise within the biomaterial of intraocular lenses (IOLs) [1][2][3][4]. Studies have reported on their clinical significance as they may deteriorate the patients' visual acuity and contrast sensitivity [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Klinische Studien haben gezeigt, dass Glistenings den Visus kaum zu reduzieren scheinen. Aber insbesondere nachts bei Vorhandensein von Gegenlicht oder unter sonnigen Bedingungen können Blendsymptome auftreten [2,3]. Mithilfe eines In-vitro-Modells wurde evaluiert, inwiefern Glistenings die Sehqualität beeinflussen.…”
Section: Einfluss Der Materialveränderungen Auf Die Optische Abbildununclassified